Performa Algoritma Bubble Sort dan Quick Sort pada Framework Flutter dan Dart SDK(Studi Kasus Aplikasi E-Commerce) - Dendi Rizka Poetra (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Sorting data is one of the techniques in data structures, and data structures certainly have various algorithms. In e-commerce applications, really need a good and efficient data sorting algorithm in terms of speed performance and also the accuracy of data sorting accuracy. In this study, the performance of the data sorting algorithm was tested, namely the Bubble Sort and Quick Sort algorithms where the supporting media for the test was an e-commerce application built with the Flutter framework and the Dart programming language. The dataset used was obtained from Optik Citra Abadi and Tokopedia's official store, namely Optik Melawai, Optik Kasoem, and Optik Seis. The test results of the two algorithms which have been divided into 5 iterations and 10 times of data retrieval from each iteration show that there is a difference in execution time for 250 data lengths, where the bubble sort algorithm takes 0.468421 seconds, while the quick sort algorithm only takes 0.008912 seconds. Both algorithms obtain 100% accuracy in the data sorting process.